2019
DOI: 10.1016/j.cemconcomp.2018.12.016
|View full text |Cite
|
Sign up to set email alerts
|

The role of porosity in external sulphate attack

Abstract: Design codes promote a limitation of permeability (indirectly of porosity) to reduce the sulphate ingress and improve the resistance of concrete and mortar to external sulphate attack (ESA). However, porosity could also have a positive effect on durability by generating additional space to accommodate the expansive phases. The aim of this study is to evaluate the role of porosity in ESA. For that, changes at the macro-scale, phase composition and pore network are monitored for mortar compositions with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 30 publications
4
22
0
Order By: Relevance
“…The pore size distribution curves presented in Figure 6 show that sulfate exposure refined the pore system, inducing a decline in 180 days mean diameter of 25.0% in OPC, 34.3% in OPC + 10GS, and 28.0% in OPC + 20GS. As noted by other researchers [ 43 , 44 ], decline is associated with a reduction in macropore volume and rises in the capillary (0.01 µm to 0.05 µm) and small capillary (0.002 µm< Φ < 0.01 μm) fractions. Such refinement was also consistent with the findings reported by Asensio et al [ 34 ], who also observed a shift in the curve to smaller diameters due to the precipitation of new compounds in the pore system and CDW masonry material pozzolanicity.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The pore size distribution curves presented in Figure 6 show that sulfate exposure refined the pore system, inducing a decline in 180 days mean diameter of 25.0% in OPC, 34.3% in OPC + 10GS, and 28.0% in OPC + 20GS. As noted by other researchers [ 43 , 44 ], decline is associated with a reduction in macropore volume and rises in the capillary (0.01 µm to 0.05 µm) and small capillary (0.002 µm< Φ < 0.01 μm) fractions. Such refinement was also consistent with the findings reported by Asensio et al [ 34 ], who also observed a shift in the curve to smaller diameters due to the precipitation of new compounds in the pore system and CDW masonry material pozzolanicity.…”
Section: Resultssupporting
confidence: 56%
“…As the data in Table 3 show, total porosity declined with exposure time by 18.7% in OPC, 20.9% in OPC + 10GS, and 24.7% in OPC + 20GS. The steeper decline in the samples bearing granite sludge was associated with their late-age pozzolanicity [27] and the precipitation of expansive compounds gypsum and ettringite in the pore system [44] that reduced permeability and retarded deterioration [45].…”
Section: Variation In Pore Structurementioning
confidence: 99%
“…The main reason that an appropriate amount of fibre can reduce the initial chloride penetration rate is that the fibre can effectively prevent the formation and development of shrinkage microcracks during the hardening process of concrete [ 36 , 37 , 38 ]. This is because the presence of microcracks significantly increases the chloride penetration rate into the concrete.…”
Section: Resultsmentioning
confidence: 99%
“…Permeation of chloride to concrete was examined in [35]. The impact of sulfate ion activity on concretes was examined in [36][37][38][39][40]. Seawater is a more complex corrosive agent than the above-mentioned agents.…”
Section: Introductionmentioning
confidence: 99%